Far‐Ranging Impact of Mountain Waves Excited Over Greenland on Stratospheric Dehydration and Rehydration. Issue 18 (18th September 2020) - Kivi, Rigel; Dörnbrack, Andreas; Sprenger, Michael; Vömel, Holger
Abstract: In situ observations of reduced stratospheric water vapor combined with those of ice particle formation are rarely conducted. On the one hand, they are essential to broaden our knowledge about the formation of polar stratospheric clouds (PSCs). On the other hand, the observed profiles allow the comparison with global circulation models. Here we report about a balloon‐borne observation above Sodankylä, Finland on 26 January 2005. The frostpoint hygrometer detected layers of reduced water vapor by up to 2 ppmv from 18.5 to 23 km. Beneath, a 1‐km‐deep layer of increased water vapor was identified. An aerosol backscatter sonde measured the presence of stratospheric ice clouds. According to meteorological analysis the PSCs were formed upstream above the east coast of Greenland due to mountain wave‐induced cooling. The inertia‐gravity waves generated a large and persistent stratospheric wake far downstream of Greenland and led to the observed dehydration. Comparing the most recent ERA5 data with operational analyses from 2005, we find an improved representation of mesoscale internal gravity waves, dehydration and PSC formation for this particular event. Plain Language Summary: This paper investigates unique in situ observations of stratospheric water vapor and combines them with nearly simultaneous optical property measurements of ice particles. The presented results reveal Antarctic‐like stratospheric dehydration and rehydration inside the Arctic polar vortex. Balloon‐borne observations of this kind are extremely rare and constitute a valuable data set for extending our knowledge about both the cloud formation processes and the representation of water vapor in global circulation models. Here, we make use of state‐of‐the art numerical weather prediction models with high spatial resolution. They allow to resolve dynamically processes that were not accessible when the observations were conducted in 2005. Besides the large‐scale cooling inside the Arctic polar vortex, it is the far‐ranging impact of the numerically resolved stratospheric mountain waves that was responsible for maintaining the thermodynamic conditions leading to the unique observations over Sodankylä, Finland. Key Points: We present unique balloon‐borne observations of stratospheric water vapor and aerosol backscatter above northern Scandinavia The balloon‐borne measurements reveal Antarctic‐like dehydration and rehydration and the existence of solid ice particles The far‐ranging impact of Greenland's mountain wave‐induced temperature fluctuations is a key process